The effect of rs776746 polymorphism in the CYP3A5 gene on heart rate when using bisoprolol in patients with acute coronary syndrome - V. A. Shumkov; K. A. Zagorodnikova; S. A. Boldueva; A. A. Murzina (Рациональная фармакотерапия в кардиологии)
Aim. The aim of this work was to study the occurrence of the rs776746 allelic variant of the CYP3A5 gene and its effect on heart rate (HR) when using bisoprolol in patients hospitalized with acute coronary syndrome (ACS).Materials and methods. The study included patients with ACS who were prescribed bisoprolol for clinical indications. All patients underwent molecular genetic testing. In order to evaluate the effectiveness of the therapy with bisoprolol, all patients underwent Holter electrocardiogram (ECG) monitoting on days 10, the following parameters were assessed: minimum, average, maximum heart rate and heart rate during an exercise test. The stress test was performed as a ladder test.Results. The study involved 97 patients (63,5±10,5 years), including 60 men and 37 women. The frequency of occurrence of the desired alleles of the CYP3A5 gene was: CYP3A5*3 - 93%, and CYP3A5*1 - 7%, which corresponds to its prevalence in the European population. 84 carriers of the CYP3A5*3*3 genotype (87%), 12 heterozygous carriers of the *1 allele (12%) and one patient with the *1*1 genotype (1%) were identified. In order to search for differences in the effects of bisoprolol depending on the genetically predetermined activity of CYP3A5, we divided the general group of patients into two subgroups: subgroup 1 (CYP3A5*3*3), represented by carriers of the genotype associated with the synthesis of the inactive form of CYP3A5, and subgroup 2 (CYP3A5*1*3 and CYP3A5*1*1), represented by carriers of at least one allele encoding the synthesis of a fully functional protein CYP3A5, coupled with an increased metabolic rate. Patients did not differ in clinical and demographic characteristics. By the time of daily ECG monitoring, both groups reached comparable heart rate values. In carriers of at least one CYP3A5*1 allele (n = 13), associated with an increased metabolic rate, the daily dose of bisoprolol on the 10th day of hospitalization was significantly higher (p <0.05). The only carrier of the homozygous CYP3A5 *1*1 variant receives bisoprolol at a daily dose of 10 mg. Taking into account the close to significant differences in glomerular filtration rate (GFR) in patients in the groups with the studied genetic variants, and the known eliminating role of the kidneys for bisoprolol, a linear regression model was built with the inclusion of factors that could affect the dose of bisoprolol: GFR, functional class of chronic heart failure, gender, age, number of simultaneously assigned CYP3A5 substrates. Of the parameters listed, only the CYP3A5 genotype significantly predicted the dose of bisoprolol (F=8.5; p<0.005; R2=0.096).Conclusion. In this study, it was demonstrated for the first time that patients with different genetic variants of CYP3A5, in particular with respect to the rs776746 polymorphism, may differ in individual requirements for the dose of bisoprolol.